1998
DOI: 10.1093/oxfordjournals.aje.a009694
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Considerations in the Use of Capture-Recapture to Estimate Prevalence: Case Studies of the Estimation of Opiate Use in the Metropolitan Area of Barcelona, Spain

Abstract: Capture-recapture, an indirect method widely used to estimate undetected populations, has been criticized because it causes problems due to a lack of compliance with several important assumptions and model selection strategies. This paper expands on the problems encountered when applying this methodology to drug abuse estimations, specifically the prevalence of opiate use in the metropolitan area of Barcelona, Spain, in 1993. Three samples of opiate users (from hospital emergency rooms, treatment centers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 22 publications
0
40
1
3
Order By: Relevance
“…As other studies have demonstrated (Hser, 1993;Domingo-Salvany et al, 1998;Platt et al, 2004;Hickman et al, 2004;Böhning et al, 2004;Chiang et al, 2007;Khazaei et al, 2012;Pérez et al, 2013;Uuskula et al, 2013), the CRC approach, despite its limitations, is useful to estimate the size of PWID populations. This approach can be of particular interest when conducted at regular intervals thus allowing for close monitoring of the injection phenomenon and optimal provision of services to this high-risk population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As other studies have demonstrated (Hser, 1993;Domingo-Salvany et al, 1998;Platt et al, 2004;Hickman et al, 2004;Böhning et al, 2004;Chiang et al, 2007;Khazaei et al, 2012;Pérez et al, 2013;Uuskula et al, 2013), the CRC approach, despite its limitations, is useful to estimate the size of PWID populations. This approach can be of particular interest when conducted at regular intervals thus allowing for close monitoring of the injection phenomenon and optimal provision of services to this high-risk population.…”
Section: Resultsmentioning
confidence: 99%
“…Using a short reference period has been suggested as a way to minimize the impact of this bias (Domingo-Salvany et al, 1998). Population movements should have been limited during the chosen one year period.…”
Section: Credibility Of the Estimatementioning
confidence: 99%
See 1 more Smart Citation
“…From 1981 to 1990 19 papers were found, whereas from 1991 to 2002, 210 publications were detected. Some recent applications of capture-recapture techniques to illicit drug use were the estimation of injecting drug users in Edinburgh, Scotland, 1992Scotland, -1994, the size of opiate use in Barcelona, Spain 1993 [5], the estimation of opiate users in Amsterdam, Netherlands, 1997 [6], the amount of drug misuse in urban and non-urban settings in the north-east of Scotland [7], and the estimation of prevalence of opiate use in Dublin, Ireland [8]. For Thailand, there have been only a few studies of this kind including a study on HIV-infected injection drug users in Bangkok 1991 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of drug use, these sources are often a hospital-like institution and the police (if there are two sources [8,9]) or treatment centers, surveys, family doctors etc. (if there are several sources [4][5][6][7]). If there are only two lists, an estimate for the population size can be constructed by multiplying the frequencies of persons identified by each list and dividing the result by the frequency of persons found on both lists, the Lincoln-Petersen estimate [10].…”
Section: Introductionmentioning
confidence: 99%